Probable airborne transmission of Burkholderia pseudomallei causing an urban outbreak of melioidosis during typhoon season in Hong Kong, China. Issue 1 (31st December 2023) - Wu, Wing-Gi; Shum, Marcus Ho-Hin; Wong, Ivan Tak-Fai; Lu, Kelvin Keru; Lee, Lam-Kwong; Leung, Jake Siu-Lun; Lao, Hiu-Yin; Lee, Annie Wing-Tung; Hau, Pak-Ting; Chan, Chloe Toi-Mei; Wong, Harmen Fung-Tin; Fung, Sharon Ka-Yee; et al.
ABSTRACT: Between January 2015 and October 2022, 38 patients with culture-confirmed melioidosis were identified in the Kowloon West (KW) Region, Hong Kong. Notably, 30 of them were clustered in the Sham Shui Po (SSP) district, which covers an estimated area of 2.5 km 2 . Between August and October 2022, 18 patients were identified in this district after heavy rainfall and typhoons. The sudden upsurge in cases prompted an environmental investigation, which involved collecting 20 air samples and 72 soil samples from residential areas near the patients. A viable isolate of Burkholderia pseudomallei was obtained from an air sample collected at a building site five days after a typhoon. B. pseudomallei DNA was also detected in 21 soil samples collected from the building site and adjacent gardening areas using full-length 16S rRNA gene sequencing, suggesting that B. psuedomallei is widely distributed in the soil environment surrounding the district. Core genome-multilocus sequence typing showed that the air sample isolate was phylogenetically clustered with the outbreak isolates in KW Region. Multispectral satellite imagery revealed a continuous reduction in vegetation region in SSP district by 162, 255 m 2 from 2016 to 2022, supporting the hypothesis of inhalation of aerosols from the contaminated soil as the transmission route of melioidosis during extreme weather events. This is because the bacteria in unvegetated soil are more easily spread by winds. In consistent with inhalational melioidosis, 24 (63.2%) patients had pneumonia. Clinicians should be aware of melioidosis during typhoon season and initiate appropriate investigation and treatment for patients with compatible symptoms.